2021
DOI: 10.1002/bdd.2297
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age, hypercholesterolemia, and the vitamin D receptor on brain endogenous β‐amyloid peptide accumulation in mice

Abstract: Age, hypercholesterolemia, and vitamin D deficiency are risk factors that increase the brain accumulation of pathogenic β‐amyloid peptides (40 and 42), precursors leading to Alzheimer's disease (AD) in humans. The relative changes accompanying aging, high cholesterol, and/or treatment of calcitriol, active vitamin D receptor (VDR) ligand, under normal physiology are unknown. We examined these relative changes in C57BL/6 mice of ages 2, 4–8, and more than 10 months old, which were fed a normal or high fat / hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 92 publications
(158 reference statements)
6
17
1
Order By: Relevance
“…The Aβ 40 concentrations in mouse brain in this study are similar to those found by Peng et al. (2021), and these values are higher than those for Aβ 42 . The ratio of Aβ 40 /β 42 concentration in mouse brain is about 2 for all ages.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The Aβ 40 concentrations in mouse brain in this study are similar to those found by Peng et al. (2021), and these values are higher than those for Aβ 42 . The ratio of Aβ 40 /β 42 concentration in mouse brain is about 2 for all ages.…”
Section: Resultssupporting
confidence: 91%
“…These mice were different from those in Peng et al. (2021) (8‐week‐old, 4‐ to 8‐month‐old, and 10‐month‐old mice).…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…Cholesterol is highly important in Aβ peptide processing in the brain (Di Paolo & Kim, 2011), the most cholesterol-rich organ, comprising ~20% of the entire cholesterol load (Björkhem & Meaney, 2004) that involves de novo synthesis independent of the liver (Jeske & Dietschy, 1980;Peng, Bukuroshi, et al, 2021).…”
mentioning
confidence: 99%
“…Separate from the established and emerging research aiming to support the shared mechanisms of vitamin D and melatonin in brain- and neurological-related disorders, there is some indication that vitamin D may play a role in amyloid [ 30 , 31 , 32 , 33 , 34 ] and tau protein [ 35 , 36 , 37 ] metabolism, which are the distinct areas that Dr. Pluta showed particular interest in, and concern about, regarding our provocative statement of query as to whether melatonin is the “next vitamin D”.…”
mentioning
confidence: 99%